2019
DOI: 10.1101/788711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retromer subunit, VPS29, regulates synaptic transmission and is required for endolysosomal function in the aging brain

Abstract: AbstractRetromer, including Vps35, Vps26, and Vps29, is a protein complex responsible for recycling proteins within the endolysosomal pathway. Although implicated in both Parkinson’s and Alzheimer’s disease, our understanding of retromer function in the adult brain remains limited, in part because Vps35 and Vps26 are essential for development. In Drosophila, we find that Vps29 Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Vps29 mutation induces mis-localization of the retromer to endosomes in the soma, which inhibits synaptic transmission (Ye et al, 2020), and genetic deficiency of SORCS2 impaired the glutamate NMDA receptor 2A (GluN2A) subunit regulating synaptic plasticity trafficking (Ma et al, 2017), other retromer components may contribute to diabetes-mediated AD-like phenotype. In conclusion, we demonstrated that APP processing and tau phosphorylation are modulated by VPS26a, and down-regulated by ROS/NF-κB/ DNMT1-mediated promoter hypermethylation in neuronal cells exposed to high glucose, which contributes to synaptic deficits, astrocyte over-activation, and cognitive impairment (Figure S8).…”
Section: Discussionmentioning
confidence: 99%
“…Vps29 mutation induces mis-localization of the retromer to endosomes in the soma, which inhibits synaptic transmission (Ye et al, 2020), and genetic deficiency of SORCS2 impaired the glutamate NMDA receptor 2A (GluN2A) subunit regulating synaptic plasticity trafficking (Ma et al, 2017), other retromer components may contribute to diabetes-mediated AD-like phenotype. In conclusion, we demonstrated that APP processing and tau phosphorylation are modulated by VPS26a, and down-regulated by ROS/NF-κB/ DNMT1-mediated promoter hypermethylation in neuronal cells exposed to high glucose, which contributes to synaptic deficits, astrocyte over-activation, and cognitive impairment (Figure S8).…”
Section: Discussionmentioning
confidence: 99%